Designing Ergonomic Learning Spaces Based on Kula Babong Local Wisdom at PAUD Restorasi Patisomba (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity is motivated by the importance of the role of learning spaces that support early childhood growth and development, especially in the early childhood education (PAUD) environment. The existence of an ergonomic learning room greatly supports children's physical and cognitive development. This is very important to apply to create a comfortable and effective learning atmosphere. However, in many places, there are still challenges in designing early childhood education spaces that are not only functional but also integrate local cultural values. The ergonomic design concept based on the local wisdom of Kula Babong is a characteristic of the architectural development of educational spaces in certain areas. This mentoring activity was attended by 12 tutors to help early childhood education tutors design a learning space that better supports the physical and psychological aspects of children. In addition, ergonomic learning rooms that accommodate the values of local wisdom and local culture can be a source of inspiration for every child's learning. The implementation of this activity was carried out through a series of design training sessions, case studies, and workshops involving teachers, architecture students, and experts in the field of ergonomics and educational space design. The results of this activity showed that as many as 12 tutors could understand the concept of ergonomic learning rooms and were used to designing ergonomic learning spaces that facilitate children's learning needs.